Elevated Macrophage Migration Inhibitory Factor (MIF) is associated with depressive symptoms, blunted cortisol reactivity to acute stress, and lowered morning cortisol - Edwards, Kate M.; Bosch, Jos A.; Engeland, Christopher G.; Cacioppo, John T.; Marucha, Phillip T. (Brain, behavior and immunity, 2010)
Macrophage Migration Inhibitory Factor (MIF) is a proinflammatory cytokine produced by leukocytes and the secretory cells of the HPA axis. Remarkably, glucocorticoids (GC) induce leukocyte MIF secretion, while MIF renders leukocytes insensitive to the anti-inflammatory effects of glucocorticoids. In light of reported associations between dysphoric states, increased inflammatory activity, and reduced GC sensitivity, the current study investigated the association between MIF, loneliness and depressive symptoms. The study further investigated the relation between plasma MIF and markers of HPA function, i.e., diurnal cortisol and the cortisol response to acute stress. Healthy university undergraduates (N=126; 64 women) were invited to participate if their scores on the Beck Depression Inventory or UCLA loneliness scale were in the upper or lower quintile of their peer group. Plasma MIF and salivary cortisol were measured in response to a public speaking task. Ambulatory diurnal cortisol was assessed for 5 consecutive days. MIF levels were 40% higher in the high-depressive symptoms group compared to the low depressive symptoms group. Elevated MIF was also associated with a smaller cortisol response to acute stress and lower diurnal morning cortisol values. The observed association between HPA function and MIF remained robust after adjustment for depressive symptoms, and demographic, anthropomorphic, and behavioural factors. High levels of depressive symptoms were likewise associated with lower morning cortisol, but this association became non-significant after adjustment for MIF. MIF may be an important neuro-immune mediator linking depressive symptoms with inflammation and HPA dysregulation.